PENGEMBANGAN MEDIA FLIPBOOK “DUNIA-KITA” HIDUP BERSAMA ALAM UNTUK MENINGKATKAN PRESTASI BELAJAR IPAS PESERTA DIDIK KELAS III SD SONOSEWU - Sintia Natasah; Arip Febrianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop a Media Flipbook (Dunia-Kita) to improve the learning achievement of Natural and Social Sciences (IPAS) students in third-grade of Sonosewu Elementary School. This research uses the R&D (Research and Development) method which refers to the ADDIE model. This research was conducted at Sonosewu Elementary School with 41 field trial students in grade III consisting of two classes, class A as many as 21 students as the control class and class B as many as 20 students as the experimental class. The data collection instruments used were observations, questionnaires and tests. The results of media feasibility were obtained from the validation of material experts with a percentage of 97.33% and media experts got a percentage of 92% in the very feasible category. The practicality of the media was obtained from the results of the teacher response questionnaire with a percentage of 97.33% and the student response questionnaire of 93.86% was included in the very practical category. The effectiveness of the media was obtained from the pretest and posttest values of the experimental and control classes. With an average pretest score of 54.75% in the experimental class, it increased to 94.6% in the posttest, while the control class increased from 53% to 83.47%, which shows an increase in higher learning achievement in the experimental class using flipbook media. Based on the results of the research, it can be concluded that the Media Flipbook (Dunia-Kita) is very feasible, practical, and effective to improve learning achievement.